Assessment of accuracy of echocardiographic parameters in prenatal diagnostics of isolated vascular ring - Pavlova, A.; Gurjeva, O.; Kurkevych, A.; Rudenko, N.; Yemec, I. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Vascular ring (VR) is hard to diagnose prenatally and requires knowledge of anatomy of the large vessels, anatomical variants of VR and special echocardiographic views. In this study we aimed to find echocardiographic parameters which may predict diagnosis of VR. From 2011 to 2017 diagnosis of the isolated VR was established prenatally and confirmed by computer tomography after birth in 39 cases (the main group). A control group comprised 47 fetuses with normal heart anatomy. The sizes of all heart structures in both groups were evaluated according to normograms corresponding to the pregnancy term and Z-scores were calculated. Our study has shown, that in both study groups Z-score for majority of heart structures were in the normal range. Despite differences in Z-scores of mitral valve annular dimensions (MV), tricuspid valve and ductus arteriosus diameter were statistically significant, this difference was not clinically relevant and did not have predictive value for VR diagnostics. This finding was confirmed using non-parametric ROC-analyses. We may conclude that only routine use of special views is an effective method of prenatal ultrasound diagnostics of VR.